FRI0380 SECUKINUMAB PROVIDES SUSTAINED IMPROVEMENT OF ENTHESITIS IN PATIENTS WITH ANKYLOSING SPONDYLITIS: POOLED ANALYSIS OF FOUR PIVOTAL PHASE 3 STUDIES. (June 2019) - Schett, Georg; Baraliakos, Xenofon; Bosch, Filip van den; Deodhar, Atul; Gensler, Lianne S.; Ǿstergaard, Mikkel; Agawane, Shital; Gupta, Ayan Das; Mpofu, Shephard; Fox, Todd; Winseck, Adam; Shete, Abhijit; et al.
Abstract : Background: Enthesitis can be a debilitating extra-articular spondyloarthritis (SpA) manifestation and cause of considerable pain and reduced quality of life/physical function. 1, 2 Objectives: To evaluate the effect of secukinumab (SEC) on axial and peripheral enthesitis in ankylosing spondylitis (AS) patients (pts) with baseline enthesitis (BLE) across all Maastricht AS EnthesiS (MASES) sites (N=13), axial MASES sites [N=11; 13 MASES minus Achilles tendons (AT); AxS], peripheral sites (N=6; AT + lateral condyles of humerus/femur; PS) and the AT (N=2; AT) at Weeks (W) 16 and 52. Methods: This post hoc analysis pooled data across 4 SEC studies in AS (MEASURE 1-4) from pts originally randomised to SEC 150mg (approved dose in AS), 300mg (MEASURE 3 only), or placebo (PBO) with BLE (MASES >0). Study designs have been reported previously. Evaluations include mean change from BL in MASES score, complete resolution (CR; MASES=0) and improvement from BL in MASES score of ≥5 counts. Mixed-effect model repeat measurement (MMRM) analysis was done on change from BL in MASES score and non-responder imputation for resolution of enthesitis at W16; data are reported as observed at W52. Results: A total of 355 (70.4%), 58 (76.3%), and 280 (72%) pts had BLE in 150mg, 300mg and PBO groups, respectively. BL characteristics were generally comparable across groups. At W16, mean change from BL for overall MASES and at AxS was greater for SEC 150mg (-2.4 and -2.3) and 300mg (-2.9 and -2.9) vs PBO (-1.9 and -1.8; P <0.05 and <0.01). At W16, pts treated with SEC 150mg (40.8% and 42.7%) and 300mg (36.2% and 42.1%) vs PBO (28.9% and 30.1%) achieved CR of enthesitis based on overall MASES and at AxS. SEC150mg and 300mg were also consistently associated with higher mean change in MASES and CR of enthesitis at PS and individually at AT vs PBO. A higher proportion of pts treated with SEC 150/300mg vs PBO achieved a higher threshold of improvement (≥5 counts) in overall MASES at W16. Further improvements were observed for all endpoints at W52 (Table). Conclusion: Secukinumab was associated with higher mean change in MASES and complete resolution of enthesitis compared to placebo at Week 16, which further improved through Week 52. References: [1] Braun J, et al.Nat Clin Pract Rheumatol. 2006;2:536-45; 2. Schett G, et al. Nat Rev Rheumatol. 2017;13:731-741. Disclosure of Interests: Georg Schett: None declared, Xenofon Baraliakos Grant/research support from: AbbVie, Boehringer Ingelheim, Bristol-Myers Squibb, Celgene, Centocor, Chugai, Janssen, MSD, Novartis, Pfizer Inc, Roche and UCB, Grant/research support from: AbbVie, Pfizer, Merck Sharp & Dohme, UCB Pharma, Novartis, Consultant for: AbbVie, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Chugai, Janssen Biologics, Novartis, Pfizer, UCB Pharma, Galapagos, Speakers bureau: AbbVie, Chugai, Janssen, Novartis, Pfizer, UCB Pharma, Filip van den Bosch Consultant for: AbbVie, BMS, Galapagos, Janssen, Lilly, Merck, Novartis, Pfizer and UCB, Speakers bureau: AbbVie, BMS, Janssen, Lilly, Merck, Novartis, Pfizer and UCB., Atul Deodhar Grant/research support from: AbbVie, Amgen, Eli Lilly, GSK, Janssen, Novartis, Pfizer, and UCB, Consultant for: AbbVie, Amgen, BMS, Eli Lilly, Janssen, Novartis, Pfizer, and UCB, Lianne S. Gensler Grant/research support from: Abbvie, Amgen, UCB Pharma, Consultant for: Novartis, Lilly, Janssen, Mikkel Ǿstergaard Grant/research support from: Abbvie, Celgene, Centocor, Merck, Novartis, Consultant for: Abbvie, BMS, Boehringer-Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo, Orion, Pfizer, Regeneron, Roche, and UCB, Speakers bureau: Abbvie, BMS, Boehringer-Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo, Orion, Pfizer, Regeneron, Roche, and UCB, Shital Agawane Employee of: Novartis, Ayan Das Gupta Employee of: Novartis, Shephard Mpofu Employee of: Novartis, Todd Fox Employee of: Novartis, Adam Winseck Employee of: Novartis, Abhijit Shete Shareholder of: Novartis Pharma AG, Employee of: Novartis Pharma AG, Brian Porter Shareholder of: Novartis, Employee of: Novartis